2011
DOI: 10.1111/j.1553-2712.2011.01122.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an Informally Structured Triage System, the Emergency Severity Index, and the Manchester Triage System to Distinguish Patient Priority in the Emergency Department

Abstract: Objectives: The objective was to compare the validity of an existing informally structured triage system with the Emergency Severity Index (ESI) and the Manchester Triage System (MTS).Methods: A total of 900 patients were prospectively triaged by six trained triage nurses using the three systems. Triage ratings of 421 (48%) patients treated only by emergency department (ED) physicians were compared with a reference standard determined by an expert panel. The percentage of undertriage, the sensitivity, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
93
3
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 22 publications
4
93
3
9
Order By: Relevance
“…Triage acuity was based on the validated emergency severity index scoring system, in which severity of illness is categorized from 1 to 5, with 1 corresponding to the highest severity and 5 corresponding to the lowest. [12][13][14][15][16] Patient disposition was classifi ed as admitted to a general practice unit, admitted to an intensive care unit (ICU), transferred to the operating room, deceased, discharged, transferred to another facility or left without completing care/against medical advice. Admissions to the general practice unit and ICU were combined for analysis of the decision to admit and ED LOS.…”
Section: Measurementsmentioning
confidence: 99%
“…Triage acuity was based on the validated emergency severity index scoring system, in which severity of illness is categorized from 1 to 5, with 1 corresponding to the highest severity and 5 corresponding to the lowest. [12][13][14][15][16] Patient disposition was classifi ed as admitted to a general practice unit, admitted to an intensive care unit (ICU), transferred to the operating room, deceased, discharged, transferred to another facility or left without completing care/against medical advice. Admissions to the general practice unit and ICU were combined for analysis of the decision to admit and ED LOS.…”
Section: Measurementsmentioning
confidence: 99%
“…[38,39] There are different studies about the accuracy, reliability and validity of 5-level triage systems for the acute patient triage. [21,[32][33][34][35][36][37] In an observational study including 486 patients by Worster et al, [36] there was no statistical difference between ESI and CTAS triage systems. In a study including 900 patients conducted by eight educated triage nurses, in which Storm-Versloot et al [33] used MTS and ESI without using a triage algorithm, it was reported that ESI had a lower triage score than MTS (11% to 20%).…”
Section: Discussionmentioning
confidence: 99%
“…[15,[29][30][31] There are various studies about accuracy, reliability and validity of acute patient triage in ATS-NTS, MTS, CTAS and ESI 5-level systems. [21,[32][33][34][35][36][37] ESI 5-level triage system which is widely used and has high value in US has been developed by emergency physicians, Richard Wuerz and David Eitel. In this system, patients are categorized from triage level 1-2 (life-threatening and critical conditions) to triage level 3-5 (diseases according to the necessities for expected sources usage).…”
mentioning
confidence: 99%
“…A análise realizada sobre a classificação de risco permite afirmar que essa ferramenta foi importante para identificar um pequeno percentual de usuários com risco iminente de morte, reconhecer os usuários com prioridade de atendimento, além da qualificação da urgência, sugerindo a importância do uso desse protocolo para estabelecer a priorização do atendimento, baseada na identificação de riscos de indivíduos 14,15 .…”
Section: Discussão|unclassified
“…Ademais, a percepção do usuário de que o profissional é quem decide por ele -se deve ou não ser atendido pelo médico -gera insatisfação e limita sua autonomia 14,15 . Além disso, há, por parte dos profissionais, dificuldades na operacionalização do protocolo, seja pela ambiência precária ou pela falta de conhecimento, por parte dos usuários, do funcionamento da classificação 16 .…”
Section: Discussão|unclassified